Syntheses of Cyclic Guanidine-Containing Natural Products - Ma, Yuyong (Tetrahedron, 2015)
Naturally occurring guanidine derivatives frequently display medicinally useful properties. Among them, the higher order pyrrole-imidazole alkaloids, the dragmacidins, the crambescidins/batzelladines, and the saxitoxins/tetradotoxins have stimulated the development of many new synthetic methods over the past decades. We provide here an overview of the syntheses of these cyclic guanidine-containing natural products.